On the Nature of the Core of α Centauri A: The Impact of the Metallicity Mixture - Nsamba, Benard; Campante, Tiago L.; Monteiro, Mário J. P. F. G.; Cunha, Margarida S.; Sousa, Sérgio G. (Frontiers in Astronomy and Space Sciences, 2019)
Forward asteroseismic modelling plays an important role towards a complete understanding of the physics taking place in deep stellar interiors. With a dynamical mass in the range over which models develop convective cores while in the main sequence, the solar-like oscillator Alpha Centauri A presents itself as an interesting case study. We address the impact of varying the metallicity mixture on the determination of the energy transport process at work in the core of Alpha Centauri A. We find that > 70% of models reproducing the revised dynamical mass of Alpha Centauri A have convective cores, regardless of the metallicity mixture adopted. This is consistent with the findings of Nsamba et al, where nuclear reaction rates were varied instead. Given these results, we propose that Alpha Centauri A be adopted in the calibration of stellar model parameters when modelling intermediate-mass stars.